Treatment with L-citrulline in patients with post-polio syndrome: study protocol for a single-center, randomised, placebo-controlled, double-blind trial - Schmidt, Simone (Trials, 2017)
BACKGROUND: Post-polio syndrome (PPS) is a condition that affects polio survivors years after recovery from an initial acute infection by the Poliomyelitis virus. Most often, patients who suffered from polio start to experience gradual new weakening in muscles, a gradual decrease in the size of muscles (muscle atrophy) and fatigue years after the acute illness. L-citrulline is known to change muscular metabolism synthesis by raising nitric oxide (NO) levels and increasing protein synthesis. This investigator-initiated, randomised, placebo-controlled, double-blind, trial aims to demonstrate that L-citrulline positively influences muscle function and increases muscular energy production in patients with PPS. METHODS/DESIGN: Thirty ambulant PPS patients will be recruited in Switzerland. Patients will be randomly allocated to one of the two arms of the study (placebo:verum 1:1). After a 24-week run-in phase to observe natural disease history and progression, participants will be treated either with L-citrulline or placebo for 24 weeks. The primary endpoint is change in the 6-min Walking Distance Test. Secondary endpoints will include motor function measure, quantitative muscle force, quantitative muscle magnetic resonance imaging and magnetic resonance spectroscopy and serum biomarker laboratory analysis DISCUSSION: The aim of this phase IIa trial is to determine if treatment with L-citrulline shows a positive effect on clinical function and paraclinical biomarkers in PPS. If treatment with L-citrulline shows positive effects, this might represent a cost-efficient symptomatic therapy for PPS patients. TRIAL REGISTRATION: ClinicalTrial.gov, ID: NCT02801071. Registered on 6 June 2016. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13063-017-1829-3) contains supplementary material, which is available to authorized users.